Condition of Contralateral Ear in Chronic Otitis Media - Peshraw Khalid Qader; Said Mustafa Said (Advanced Medical Journal)
Background and objectives: Chronic otitis media is defined as a continuous and enduring inflammation and infection of middle ear cleft and mastoid air cells for more than 6 weeks. It is characterized by its destructive disease of middle ear in nature. The contralateral ear is defined as an ear that the patient does not complaining off, because of either ignorance or not causing discomfort in comparison to the diseased ear, or it may be totally normal and have nothing to complain. The aim of this study was to declare the condition of contralateral ear in chronic otitis media.